Autoantibody to nerve tissue in a patient with a peripheral neuropathy and an IgG paraprotein. Issue 10 (October 1981) - Sewell, H F; Matthews, J B; Gooch, E; Millac, P; Willox, A; Stern, M A; Walker, F
Abstract : The antibody activity of a benign IgG lambda paraprotein to nerve tissue in a case of peripheral neuropathy has been investigated using immunohistochemical methods on tyrpsin-treated, formalin-fixed, paraffin-embedded tissue. IgG lambda was found in th sural nerve biopsy of the patient. Specific binding of the purified IgG lambda paraprotein and its isolated F(ab')2 fragment to homologous nerve and brain tissue was demonstrated. Similar activity was not demonstrable on fresh frozen cryostat sections. The results suggest that tests for autoantibodies to nerve tissue in neuropathological disorders should not be confined to fresh frozen tissue substrates.